Treatment of patients with painful blind eye using stellate ganglion block - Tatiana Vaz Horta Xavier; Thiago Robis de Oliveira; Tereza Cristina Bandeira Silva Mendes (Brazilian Journal of Anesthesiology, 2016)
Background and objectives: management of pain in painful blind eyes is still a challenge. Corticosteroids and hypotensive agents, as well as evisceration and enucleation, are some of the strategies employed so far that are not always effective and, depending on the strategy, cause a deep emotional shock to the patient. Given these issues, the aim of this case report is to demonstrate a new and viable option for the management of such pain by treating the painful blind eye with the stellate ganglion block technique, a procedure that has never been described in the literature for this purpose. Case report: six patients with painful blind eye, all caused by glaucoma, were treated; in these patients, VAS (visual analogue scale for pain assessment, in which 0 is the absence of pain and 10 is the worst pain ever experienced) ranged from 7 to 10. We opted for weekly sessions of stellate ganglion block with 4 mL of bupivacaine (0.5%) without vasoconstrictor and clonidine 1 mcg/kg. Four patients had excellent results at VAS, ranging between 0 and 3, and two remained asymptomatic (VAS = 0), without the need for additional medication. The other two used gabapentin 300 mg every 12 h. Conclusion: currently, there are several therapeutic options for the treatment of painful blind eye, among which stand out the retrobulbar blocks with chlorpromazine, alcohol and phenol. However, an effective strategy with low rate of serious complications, which is non-mutilating and improves the quality of life of the patient, is essential. Then, stellate ganglion block arises as a demonstrably viable and promising option to meet this demand. Resumo: Justificativa e objetivos: O manejo da dor em olhos cegos dolorosos ainda é um desafio. Corticosteroides e hipotensores, bem como evisceração e enucleação, são algumas das estratégias até então empregadas, nem sempre eficazes e que, a depender da estratégia, causam um profundo abalo emocional no paciente. Dadas essas questões, o objetivo deste relato de caso é demonstrar uma nova e viável opção para o manejo desse tipo de dor por meio do tratamento do olho cego doloroso com bloqueios de gânglio cervicotorácico, técnica nunca descrita na literatura para esse fim. Relato de caso: Foram tratados seis pacientes portadores de olho cego doloroso, todos por glaucoma, nos quais a EVA (escala visual analógica para avaliação da dor em que 0 é ausência de dor e 10 é a maior dor já experimentada) variava de 7 a 10. Optou-se por sessões semanais de bloqueio de gânglio cervicotorácico com 4 mL de bupivacaína (0,5%) sem vasoconstritor e clonidina 1 mcg/Kg. Quatro pacientes apresentaram excelente resultado EVA, com variação entre 0 e 3, e dois permaneceram assintomáticos (EVA = 0), sem necessidade de medicação suplementar. Os outros dois usaram gabapentina 300 mg de 12 em 12 horas. Conclusão: Atualmente, várias são as opções terapêuticas para o tratamento do olho cego doloroso, entre as quais se destacam os bloqueios retrobulbares com clorpromazina, álcool e fenol. No entanto, uma estratégia eficaz, com pequeno índice de complicações graves, não mutilante e que melhore a qualidade de vida do paciente é imprescindível. O bloqueio do gânglio cervicotorácico surge, pois, como uma opção comprovadamente viável e promissora para atender a essa demanda. Keywords: Eye pain, Pain management, Nerve block, Palavras-chave: Dor ocular, Manejo da dor, Bloqueio nervoso